2013
DOI: 10.1111/cas.12097
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells and tumor blood volume as predictors in lung cancer

Abstract: The current criteria for evaluating antiangiogenic efficacy is insufficient as tumor shrinkage occurs after blood perfusion decreases. Tumor blood volume (BV) in computed tomography perfusion imaging and circulating endothelial cells (CEC) might predict the status of angiogenesis. The present study aimed to validate their representation as feasible predictors in non-small-cell lung carcinoma (NSCLC). A total of 74 patients was categorized randomly into two arms undergoing regimens of vinorelbine and cisplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
3
22
1
Order By: Relevance
“…The authors reported a positive correlation of baseline counts with good prognosis. After all, in congruence with other works, a decrease in both circulating EnC and EPC correlated with a longer PFS or OS in the majority of studies, before and after effective anti-angiogenic therapy and/or chemotherapy [85,86] Polyploidy is a common cellular cancer marker and has been included into investigations on circulating EnC [34,87,88]. Latest work on the topic may come from Zhang et al [88], employing Cytelligen's SE-iFISH to identify PD-L1 positive, aneuploid circulating EnC (multiploidy in chromosme 8) assumed to be tumor-associated and investigating their usefulness as companion diagnostic as to predict resistance to checkpoint blockade immunotherapy in advanced NSCLC patient [88].…”
Section: Endothelial Cell Clinical Usesupporting
confidence: 84%
“…The authors reported a positive correlation of baseline counts with good prognosis. After all, in congruence with other works, a decrease in both circulating EnC and EPC correlated with a longer PFS or OS in the majority of studies, before and after effective anti-angiogenic therapy and/or chemotherapy [85,86] Polyploidy is a common cellular cancer marker and has been included into investigations on circulating EnC [34,87,88]. Latest work on the topic may come from Zhang et al [88], employing Cytelligen's SE-iFISH to identify PD-L1 positive, aneuploid circulating EnC (multiploidy in chromosme 8) assumed to be tumor-associated and investigating their usefulness as companion diagnostic as to predict resistance to checkpoint blockade immunotherapy in advanced NSCLC patient [88].…”
Section: Endothelial Cell Clinical Usesupporting
confidence: 84%
“…The later study by Li et al [78] included a total of 85 patients with locally advanced or metastatic NSCLC who underwent NP chemotherapy, alone or combined with rh-endostatin. In the chemotherapy group, the aCECs values were negatively correlated with the tumor progression time (p = 0.036) in the combined treatment group.…”
Section: Circulating Endothelial Cells (Cec)mentioning
confidence: 99%
“…Another clinical study on NSCLC patients treated with anti-angiogenic chemotherapy also showed that tumour vascular volume was reduced significantly in responders versus non-responders [40] . In addition, decreased tumour blood volume during antiangiogenic therapy was associated with a clinic benefit in lung cancer patients [41] .…”
Section: Discussionmentioning
confidence: 99%